2015
DOI: 10.5493/wjem.v5.i2.84
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Wnt/β-catenin pathway in gastric cancer: An in-depth literature review

Abstract: Gastric cancer remains one of the most common cancers worldwide and one of the leading cause for cancerrelated deaths. Gastric adenocarcinoma is a multifactorial disease that is genetically, cytologically and architecturally more heterogeneous than other gastrointestinal carcinomas. The identification of specific membrane, intracellular, and extracellular components of the Wnt pathway has revealed potential targets for gastric cancer therapy. High-throughput "omics" approaches will help in the search for Wnt p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
230
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 262 publications
(235 citation statements)
references
References 249 publications
2
230
1
2
Order By: Relevance
“…Recently, researchers have demonstrated that 30-50% of GC cases are associated with the abnormal activation of the Wnt/β-catenin signaling pathways (16,17). The TCF/LEF axis serves a crucial role in the Wnt/β-catenin signaling pathway (18).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, researchers have demonstrated that 30-50% of GC cases are associated with the abnormal activation of the Wnt/β-catenin signaling pathways (16,17). The TCF/LEF axis serves a crucial role in the Wnt/β-catenin signaling pathway (18).…”
Section: Introductionmentioning
confidence: 99%
“…GC is a multifactorial disease resulting from the interaction between genetic and environmental factors at the stomach mucosa level. 9 Cutsem EV et al stated that, a genetic basis causative mutations in CDH1 has been found in only around 40% of families affected by hereditary diffuse GC. GC have been found in people with other hereditary cancer syndromes, such as gastric adenocarcinoma and proximal polyposis of the stomach syndrome, and in those with mutations in TP53 (Li-Fraumeni syndrome), APC (familial adenomatous polyposis), or STK11 (Peutz-Jeghers syndrome).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, most GC patients are diagnosed in advanced-stage disease with a poor prognosis. 9 Common symptoms are weight loss, epigastric pain, vomiting, nausea, anorexia, dysphagia, bloating, and regurgitation. It was often initially misdiagnosed as dyspepsia syndrome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have focused in other components of the pathway and their contribution to cancer development. For example, APC, β-catenin, AXIN, WTX and TCF4 also contribute to the development of certain types of cancer [10,11].…”
Section: Comment and Discussionmentioning
confidence: 99%